(untitled) (AYUSHDHARA, 2020)
Motherhood is an eternal blessing. In today’s era due to competitive life, new generation desire only one child bestowed with good health, supreme intellect and wisdom. But, in today’s effluent societies, due to carrier orientation and busy life schedule, people are not paying attention towards marital age, healthy daily routine, seasonal regimen and outcome of these unhealthy habits is emerging out in the form of various disorders influencing physical, psychological and reproductive outcome. So, it is the need of hour to revitalize the ancient methods of health care to obtain its prime benefits for mankind. Ayurveda, The oldest ancient wisdom takes care of all aspects of human beings and has described compendious preconceptional care approach for getting excellent progeny. Although preconceptional care mentioned in Ayurveda classics is time tested, scientific, invincible, undoubtable preventive approach but today’s era is era of evidence based practice thereby requires to prove its relevance on scientific parameters by shifting the basis for decision making from tradition to firmly grounded scientific research. On detailed analysis of the concept, it was found that every single fact pertaining to preconceptional care mentioned in Ayurvedic context is scientific in terms of modern scientific knowledge. So, this paper summarizes the scientific revalidation of risk behaviour responsible for negative traits as well as of preventive care approach in present era to make it globally acceptable excellent preventive strategy for getting healthy progeny.